Transdisciplinary and Cosmopolitical Reflections on the Sociology of Religion and Culture in Germany (KULT_online, 2009)
This volume is based on the eponymous lecture series ("Come-back of Religion or Secular Culture? Sociology of Culture and Religion Today") that took place at the Freie Universität Berlin's Institute of Sociology in summer 2006. After laying out some general issues pertaining to 'universality' and 'territoriality', the authors focus on specific challenges confronting the sociologies of culture and religion. Finally, they analyse the place of culture and religion in our lives. The articles cover a variety of themes and methodologies, but each addresses the inherent question: What is the position of sociology in the sciences?This volume is recommended for students seeking an overview of current issues in the sociology of religion and culture, and includes bibliographies to guide more in-depth research.